A study of ABO Haemolytic Disease of the newborn in Hospital Of Universiti Sains Malaysia Kelantan. - Mohd Sahid, Salman (2001)
The study was to evaluate whether the routine serological and haematological laboratory tests could be used for an early diagnosis of ABO HDN and to obtain epidermiologicaI data. This is a comparative cross-sectional study of newborn babies born to blood group 0 rhesus positive mothers in labour room of HUSM from October, 2000 to June, 2001. Specimens from cord blood of suitable babies were collected and investigated for haemoglobin, bilirubin, reticulocytes count, DAT, spherocytes count and NRBC per 100 WC. The results were analysed statistically. The clinical features and management data of ABO incompatible babies were taken from management file and correlation made with the cord's blood findings. The incidence and severity of ABO HDN were also estimated from the data. Altogether 85 babies ie 34 ABO incompatible and 51 ABO compatible. The haemoglobin, spherocytes count and DA T showed a statistically significant difference between ABO incompatible and ABO compatible babies. Clinically five babies of ABO incompatible noted to be jaundice with two of them received phototherapy but exchange transfusion was not needed in any of them. The incidence of ABO incompatible infants in HUSM is 15.6%. The incidence of ABO HDN is 2.3%. The incidence of ABO incompatible infants requiring phototherapy due to ABO HDN is 6.7% and the incidence of all infants requiring phototherapy due to ABO HDN is 0.92%. There is poor correlation between the cl inical features and laboratory findings. The cord blood tests therefore can not be recommended as method of early diagnosis of ABO HDN. The cord blood tests were not sensitive and specific probably due to mildness of ABO HDN in HUSM. The incidence and severity of ABO HDN here are almost comparable to the figures of North America and Europe.